The Implementation of the Japanese and the German Culture into the Operation Hungarian Firm - Nagy, Tamás Zoltánné (International Journal of Engineering and Management Sciences, 2016)
How can the Japanese culture be implemented into the operation of a firm - partly a German property working in Hungary. In my presented arcticle I have studied various organisational culture models, and compared them to the culture of our enterprise, seeking for similarities and contraries. I have studied the environmental factors and resources which have an effect on our production. During the investigation I have also considered how can we harmonize cultures of different nations and how it affects the production on the whole. I have also investigated the installation of robots, and searched for the solution how we can make our production much more economical. Due to the persistent decrease of population, and leck of professionals, the use of robots is neccessary to fulfill the customer requirements in time, with the sufficient quantity and required quality of goods. According to the Japanese Toyota-method,theautomatization of a technology can only be successful, if it is tested at least ten times, but –beacuse of the leck of time- we do not have the possibility of it. As the manufacturing parameters and observations have not developed the proper way, the scrap rate is higher than it is at firms, where is more available time for the building up of the technology.